Pemanfaatan Quizizz dalam Pembelajaran Matematika SMP untuk Meningkatkan Pemahaman Konsep dan Kemampuan Pemecahan Masalah - Cita Indra Mahardika; Maryati, Iyam (Jurnal Pendidikan Matematika : Judika Education, 2026)
Mathematics learning at the junior high school (SMP) level requires instructional strategies that are capable of optimally enhancing students’ conceptual understanding and mathematical problem-solving abilities. One digital learning medium that has been widely utilized in the context of mathematics instruction is Quizizz. This study aims to systematically review empirical research examining the use of Quizizz in mathematics learning, particularly in relation to improving conceptual understanding and problem-solving skills of junior high school students. The research employed a Systematic Literature Review (SLR) method by analyzing relevant scientific articles published in nationally accredited journals and reputable international journals. The process of literature search and article selection was conducted in a structured manner based on predetermined inclusion and exclusion criteria. The findings indicate that the use of Quizizz in junior high school mathematics learning, whether integrated with active learning models or implemented as an interactive assessment medium, tends to contribute positively to the enhancement of students’ conceptual understanding and mathematical problem-solving abilities. These results suggest that Quizizz has strong potential as an effective learning medium to support mathematics instruction at the junior high school level.   Keywords: Quizizz, Conceptual Understanding, Problem-Solving Ability, Mathematics, Junior High School, Systematic Literature Review.